The commerce of war - Coffee, Neil (University of Chicago Press, 2009)
Latin epics such as Virgil's Aeneid, Lucan's Civil War, and Statius's Thebaid addressed Roman aristocrats whose dealings in gifts, favors, and payments defined their conceptions of social order. In The Commerce of War, Neil Coffee argues that these exchanges play a central yet overlooked role in epic depictions of Roman society. Tracing the collapse of an aristocratic worldview across all three poems, Coffee highlights the distinction they draw between reciprocal gift giving among elites and the more problematic behaviors of buying and selling. In the Aeneid, customary gift and favo
Includes bibliographical references and index
Keywords: Statius; P. Papinius; Virgil; Lucan; Thebais; Aeneis; Pharsalia; Negotiation; Reciprocity (Commerce); War in literature